The Effect of Financial Performance on Firm Value: Dividend Policy's Moderating Role - R.Win, Daniel Erinaldi.; Hasibuan, Henny Triyana (E-Jurnal Akuntansi, 2024)
The rapid economic growth in Indonesia has markedly influenced corporate performance. This study aims to provide empirical evidence concerning the effects of liquidity, leverage, activity, profitability, and dividend policy on firm value. A purposive sampling technique was utilized for this research. Data were gathered through non-participant observational methods. Utilizing SPSS software, the researchers conducted a moderation regression analysis on the acquired data. The findings indicate that liquidity, leverage, and profitability do not significantly affect firm value. However, activity was shown to impact firm value, whereas dividend policy does not alter the relationship between liquidity, leverage, and activity on firm value. Interestingly, dividend policy does enhance the effect of profitability on firm value. Keywords: Firm Value; Financial Performance; Dividend Policy